PERAN PROGRAM TAHFIZ DAN TAHSIN AL-QUR’AN DALAM MENINGKATKAN LITERASI AL-QUR’AN SISWA DI MADRASAH IBTIDAIYAH NURUL UMMAH KOTAGEDE YOGYAKARTA - Muhammad Shaleh Assingkily (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2019)
The literacy study of the Qur'an which was implemented in the Tahfiz program and tahsin at MI Nurul Ummah Kotagede Yogyakarta to see the role of the Tahfiz and Tahsin program in improving the literacy of the Al-Qur' an in MI Nurul Ummah. This study uses a qualitative approach. The results showed that the Tahfiz and Tahsin program played a significant role in improving Qur'anic literacy for students, this was seen from: first, the creation of a Koranic learning atmosphere at MI Nurul Ummah Kotagede Yogyakarta, secondly, through the implementation of the Tahfiz and Tahsin program to grow the spirit of religious practice for students. The concrete efforts are: (1) Routine activities at the madrasa, (2) Supervision of parents of students at home, (3) Allocation of adequate tahfiz / tahsin learning time, (4) Tahfiz / tahsin teaching staff (every 10-12 students 1 accompanying teacher), (5) intense communication between madrasas and parents of students (Utilizing communication via the WhatsApp Group and regular meetings every two months).